Comparative Feasibility and Environmental Life Cycle Assessment of Cotton Stalks Gasification and Pyrolysis - Ioannis Vaskalis; Anastasia Zabaniotou (Biomass, 2024)
In a circular economy, significant emphasis is given to the energetic valorization of agricultural byproducts. Cotton stalks are suitable as a feedstock for the production of bioenergy due to their high energy content. This study’s main focal areas are the economic viability and environmental implications of a system that can gasify or pyrolyze 25,500 tons of cotton stalk annually. To learn more about how gasification and pyrolysis affect the environment, a life cycle assessment (LCA) was conducted. This analysis evaluates the whole value chain and covers all stages of the cotton supply chain from cradle to gate, including production, harvest, transportation, and utilization. According to the findings, both systems exhibit economic viability, generating sizable profits and having quick payback times. However, despite its larger initial expenditure of EUR 2.74 million, the pyrolysis unit ends up being the better option because it has a payback period of 1.58 years, a return on investment (ROI) of 58% and a net present value (NPV) of EUR 21.5 million. Gasification is still an economically attractive alternative with a lower initial investment (EUR 1.81 million), despite having a lower ROI (36%) and NPV (EUR 10.52 million), as well as a longer payback period (2.41 years). However, the environmental implications of the gasification option are generally higher than those of pyrolysis. The impacts of gasification on fossil depletion (FDP) were estimated to be 5.7 million kg oil eq., compared to 5.3 million kg oil eq. for pyrolysis. Similarly, gasification resulted in 41.55 million kg U235 eq. and pyrolysis in 41.5 million kg U235 eq. related to impacts on ionizing radiation (IRP_HE). Other impact categories that emerge as the most important are freshwater eutrophication (FEP) and marine eutrophication (MEP).